2019
DOI: 10.3144/expresspolymlett.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

Improving and predicting the mechanical properties of foamed and stretched composite poly(lactic acid) films

Abstract: Foamed poly(lactic acid) films reinforced with micro-crystalline cellulose (MCC), were uniaxially stretched to different ratios. At 10% (weight) loading MCC particles gave an approximately 3.5 times improvement in stiffness over unreinforced foams. X-ray tomography and image analysis showed that most MCC particles had low aspect ratios, were randomly oriented and well distributed. Stretching did not change the orientation of the MCC particles. Increases in stiffness with stretching were due to the alignment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, beyond 3 wt.% CNF concentration, increase in stiffness which limited the foaming of the polymers was observed. Hussain and Dickson 80 recorded about 3.5 times the original stiffness value due to strain hardening effects when semicrystalline PLA was reinforced with microcrystalline cellulose (MCC) at about 10 wt.% loading and foamed with liquid CO 2 in the batch process. Uniaxially stretching the foams at different ratios showed that MCC was randomly oriented and well dispe rsed within the PLA matrix.…”
Section: Introductionmentioning
confidence: 99%
“…However, beyond 3 wt.% CNF concentration, increase in stiffness which limited the foaming of the polymers was observed. Hussain and Dickson 80 recorded about 3.5 times the original stiffness value due to strain hardening effects when semicrystalline PLA was reinforced with microcrystalline cellulose (MCC) at about 10 wt.% loading and foamed with liquid CO 2 in the batch process. Uniaxially stretching the foams at different ratios showed that MCC was randomly oriented and well dispe rsed within the PLA matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer foams are two-phase materials with statistically distributed macromolecular size gas bubbles in the polymer [1]. Polymer foams are most commonly made from polyurethane (PU), polystyrene (PS), polyethylene (PE), polyvinyl-chloride (PVC) and polypropylene (PP), but nowadays, the use of polylactic acid (PLA) is increasing continuously as well [2][3][4][5]. Polymer foams have different properties depending on manufacturing technology, the amount and size of gas bubbles, and the applied solid matrix material, but they have considerably lower density than solid polymers (10-400 kg/m 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polymer foams have different properties depending on manufacturing technology, the amount and size of gas bubbles, and the applied solid matrix material, but they have considerably lower density than solid polymers (10-400 kg/m 3 ). In general, they are good insulators of heat and sound, resistant to chemicals, and have good impact damping properties [2][3][4][5]. For this reason, engineering foams are mostly used in the packaging, automotive, electronic, building, toy, leather and shoe industries, as well as for producing sporting and household goods [6].…”
Section: Introductionmentioning
confidence: 99%
“…Polylactic acid (PLA) is a natural polymer produced from fermented starch of corn, rice, wheat, or sugarcane and can be used in many applications such as in formation of bottles, films, food packaging, and service ware. PLA is biodegradable and has good process ability and good optical properties 4,5 . However, PLA is too brittle to be used as thin films, 6 therefore, to increase the flexibility of PLA it could be blended with LDPE and starch and our newly prepared bioblend film with further modification in properties will be shown in our study.…”
Section: Introductionmentioning
confidence: 91%